2015
DOI: 10.1016/j.clml.2015.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Tyrosine Kinase Inhibitors and Molecular Monitoring Patterns in Newly Diagnosed Patients With Chronic Myeloid Leukemia in the Community Setting

Abstract: Dasatinib and nilotinib were more effective than imatinib as first-line therapy for CML in a community setting, as observed in descriptive and univariate analyses. The frequency of cytogenetic and molecular monitoring was lower than that recommended by current guidelines, including patients with no molecular or cytogenetic assessments during the 18-month follow-up. Therefore, MSH/USON is working toward improving compliance with response monitoring guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…By 12 months, 61% patients achieved CCyR or MMR compared to only 38% treated with imatinib. Time to MMR is also significantly higher in dasatinib and nilotinib than imatinib [113].…”
Section: Dasatinib Nilotinib Bosutinib and Radotinib (Bcr-abl Tkis)mentioning
confidence: 92%
See 2 more Smart Citations
“…By 12 months, 61% patients achieved CCyR or MMR compared to only 38% treated with imatinib. Time to MMR is also significantly higher in dasatinib and nilotinib than imatinib [113].…”
Section: Dasatinib Nilotinib Bosutinib and Radotinib (Bcr-abl Tkis)mentioning
confidence: 92%
“…As TKI is a drug class that has to be administrated over a long period of time, the lack of follow-up during the course of treatment is a problem that could limit the effectiveness. In a study reporting effectiveness of TKIs in CML patients in a community setting, it is found that cytogenetic and molecular response monitoring assessments were conducted less frequently than recommended [113]. Poor monitoring may result in delay in adjustments in treatment plan.…”
Section: Lack Of Follow-up and Nonadherencementioning
confidence: 99%
See 1 more Smart Citation
“…[40] A retrospective study of 300 patients with CML-CP treated in community practices of the McKesson Specialty Health/US Oncology Network between July 2007 and September 2012 found that only half of patients had molecular monitoring at any time during the observation period, and only 23% had monitoring by an IS-standardized laboratory. [41] The adoption of IS-standardized reporting by US-based clinical diagnostic laboratories, although initially quite slow (with only 29% of laboratories selfreporting IS use in 2012), has been progressively increasing. [13] If variability in BCR-ABL1 RQ-PCR testing across laboratories is not standardized in the minority of US laboratories not using the IS, the results from these laboratories will not be translatable to consensus clinical actions.…”
Section: Molecular Monitoring In the United States: Current Statusmentioning
confidence: 99%
“…However, most studies evaluating the efficacy and safety of first‐line nilotinib treatment in patients with CML‐CP are clinical trials with rigorous study designs and stringent patient eligibility criteria (Saglio et al , ; Kantarjian et al , ; Giles et al , ; Hochhaus et al , , ). Hence, there is a lack of real‐world data supporting the effectiveness and safety of frontline nilotinib therapy in CML‐CP (Di Bella et al , ). Furthermore, there is also a lack of quantitative information available regarding adherence to nilotinib therapy, and which modalities of administration have been suspected to impair regular intake (Di Bella et al , ).…”
mentioning
confidence: 99%